Cardiac Involvement in Thoracic Lymphoma - Rossana Izzo; Daniela Campanale; Mattia Duchini; Angelo Di Simone; Andrea Menafoglio; Andrea Demarchi (Clinical Case Reports)
ABSTRACT This case highlights the role of cardiac imaging in detecting the evolution of cardiac involvement during thoracic lymphoma and the importance of optimal chemotherapy, which leads to a rapid improvement of the cardiac dysfunction, without the need for cardiac pharmacotherapy.